Internet of Things and Analytics for Agriculture, Volume 3 - Pattnaik, Prasant Kumar; Kumar, Raghvendra; Pal, Souvik; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book discusses one of the major challenges in agriculture which is delivery of cultivate produce to the end consumers with best possible price and quality. Currently all over the world, it is found that around 50% of the farm produce never reaches the end consumer due to wastage and suboptimal prices. The authors present solutions to reduce the transport cost, predictability of prices on the past data analytics and the current market conditions, and number of middle hops and agents between the farmer and the end consumer using IoT-based solutions. Again, the demand by consumption of agricultural products could be predicted quantitatively; however, the variation of harvest and production by the change of farm's cultivated area, weather change, disease and insect damage, etc., could be difficult to be predicted, so that the supply and demand of agricultural products has not been controlled properly. To overcome, this edited book designed the IoT-based monitoring system to analyze crop environment and the method to improve the efficiency of decision making by analyzing harvest statistics. The book is also useful for academicians working in the areas of climate changes.
IoT: Foundations and Applications -- Functional Framework for IoT-based agricultural system -- Field monitoring and automation system -- Agriculture Sensor Network: Infrastructure, protocols and standards -- Implementation of sensors and RFID for disease and pest control -- Sensor-based Precision agriculture, Sensor data acquisition. .
Keywords: Internet of things; Artificial intelligence; Agriculture$1 (BEconomic aspects.s; Sustainability; Internet of Things; Artificial Intelligence; Agricultural Economics; Sustainability; Artificial intelligence -- Agricultural applications; Internet of things